Semaphorin 3A alters endothelial cell immunogenicity by regulating Class II transactivator activity circuits. Issue 8 (28th March 2014) - Schlahsa, Laura; Zhang, HaiJiao; Battermann, Anja; Verboom, Murielle; Immenschuh, Stephan; Eiz‐Vesper, Britta; Stripecke, Renata; Engelmann, Katrin; Blasczyk, Rainer; Figueiredo, Constança
<x xml:space="preserve">Abstract</x> Background Endothelial cells (ECs) play a pivotal role in the allogeneic immune response upon transplantation. Semaphorin 3A (Sema3A) was implicated in the modulation of EC growth, but its effects on immunogenicity were not previously investigated. Study Design and Methods ECs were transduced with a lentiviral vector encoding for the green fluorescence protein (GFP) sequence under the control of a Class II transactivator (CIITA)‐dependent promoter. Upon stimulation of nonmodified ECs with recombinant Sema3A protein, mRNA and protein levels of CIITA, HLA‐DR, and Sema3A receptors were evaluated. An enzyme‐linked immunosorbent assay was developed to quantify Sema3A levels in the sera of kidney‐transplanted patients. Results Sema3A stimulation of lentiviral vector encoding for the GFP sequence ECs caused a significant up regulation of the transgene expression, indicating an increase in CIITA levels. Stimulation of nonmodified ECs with Sema3A resulted in an up regulation of CIITA expression, which was associated with enhanced HLA‐DR levels and an increase in alloreactive CD4+ T‐cell proliferation. Sema3A receptor expression was enhanced by CIITA, establishing a positive feedback loop. Higher levels of Sema3A were observed in sera of patients presenting with organ rejection. Conclusion This study links Sema3A signaling in ECs with increased CIITA levels and higher HLA‐DR expression, resulting in CD4+ T‐cell activation, which might have important implications for tissue and organ transplantation.